Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar Rupiah terhadap Return Saham pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia (2018-2020) - Wahyu Citra Ananda; Agus Budi Santoso (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study is to analyze the effect of inflation, interest rates and exchange rates on stock returns in banking companies listed on the IDX for the period (2018-2020). The method used in this study is multiple regression analysis, which is an analysis used to determine the influence of each independent variable on the dependent variable. With the aim of getting a comprehensive picture of the effect of inflation, interest rates and exchange rates on stock returns. The population in this study was banking companies listed on the Indonesia Stock Exchange in the research period 2018 – 2020.The samples in this study were taken using purposive sampling techniques and the data used were secondary data in the form of financial statements for the period 2018 - 2020 published on the Indonesia Stock Exchange, Indonesian Capital Market Directory (ICMD) and Indonesian stock exchange (idx). The results of this study are inflation has a positive andsignificant effect on stock returns, interest rates have a negative and significant effect on stock returns and exchange rates have a positive and significant effect on stock returns in banking companies listed on the IDX for the 2018-2020 period.